2009 IEEE/RSJ International Conference on Intelligent Robots and Systems 2009
DOI: 10.1109/iros.2009.5354155
|View full text |Cite
|
Sign up to set email alerts
|

Human-robot collaboration in cellular manufacturing: Design and development

Abstract: The challenge of this work is to study the design and development of human-robot collaboration (HRC) in cellular manufacturing. Based on the concept of human collaborative design, four main design factors are being identified and developed in an active HRC prototype production cell for cable harness assembly. Human collaborative design aims to optimize the system design for the advantage of collaboration between human and robots based on human considerations. Task modeling approach is developed to study and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 17 publications
2
57
0
1
Order By: Relevance
“…These include: tool connection/disconnection (1,8), ball insertion (2, 3, 7), joint pivoting (4, 5), vision triggered emergency stop (6), and joint manual unmounting (9,10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include: tool connection/disconnection (1,8), ball insertion (2, 3, 7), joint pivoting (4, 5), vision triggered emergency stop (6), and joint manual unmounting (9,10).…”
Section: Resultsmentioning
confidence: 99%
“…Papakostas et al [8] discuss the key features of cooperating robotic cells in automotive assembly, and provide simulated comparisons of two scenarios: a conventional welding robotic cell, and one with cooperating robots. The authors of [9] assess five alternative safety designs, covering both hardware and control design, of a human-robot collaboration prototype cell for cable harness assembly. In [10], a new cell production assembly system, with human-robot cooperation is developed.…”
Section: Research On Human-machine Cooperation In the Industrymentioning
confidence: 99%
“…This is not only to provide cheaper and easily applicable feedback systems can replace full force feedback with none or small performance reduction, but also to resolve fundamental issues such as stability in closed loop [Tegin and Wikander, 2005]. In addition, such sensory substitution techniques can also be used to provide the human with feedback about the advanced robotic perception of the environment (e.g., depth sensors [Plagemann et al, 2010]), that may not be covered by the human sensory system.…”
Section: Interfaces For Improved Human Perceptionmentioning
confidence: 99%
“…In the field of industrial robotics, many manufacturing applications are also reported in literature, ranging from load-ing and transporting heavy wheels [Levratti et al, 2016], collaborative assembly of a homokinetic mechanical joint [Cherubini et al, 2013, Cherubini et al, 2016 and cellular phones [Tan et al, 2009]. Another application within this field was presented in [Erden and Billard, 2014].…”
Section: Benchmarking and Relevant Use Casesmentioning
confidence: 99%
See 1 more Smart Citation